Modelling the Impact of Climate Change on Agricultural Productivity: Case Studies from Developing Nations - Gupta, Aarav Sharma; Kumar, Rahul; Desai, Meera; Shah, Rohan; Mehta, Neha (International Journal of Technology and Modeling, 2023)
Climate change poses a significant threat to agricultural productivity, particularly in developing nations where agriculture remains a primary livelihood source. This study presents a comprehensive modelling approach to assess the impact of climate variability on agricultural output, with a focus on case studies from India. Using a combination of climate projection data, crop simulation models, and econometric analyses, the research evaluates changes in temperature, precipitation patterns, and extreme weather events, and their implications for key staple crops such as rice and wheat. The study highlights regional disparities in vulnerability, adaptive capacity, and yield outcomes across different agro-climatic zones in India. Results indicate that without effective adaptation strategies, agricultural productivity could decline significantly in the coming decades, exacerbating food insecurity and rural poverty. The findings underscore the urgency of integrating climate resilience into national agricultural policies and promoting climate-smart agricultural practices. This research contributes to a broader understanding of how climate change affects agriculture in developing contexts and offers a methodological framework applicable to other regions facing similar challenges.